Multi Story Housing - Ehab Hamza Khzemieh; Hamza Abdullah Wahdan; Mohammad Jaber Salim; Mohammad Nadim Dawwas (My University, 2014)
Perhaps the urgent need to pursue the rapid technical development in various construction industries which are still witnessing a remarkable progress of time, and discoveries of modern construction, which aims primarily to achieve human well-being, taking into account the growing interest in environmental aspects including the design of green buildings and the resistance to earthquakes, according to planning Strategic Sustainable DevelopmentAs for the engineering department of buildings, you can define a building's architecture as a link between the Architecture, Planning and Landscape Architecture, and between the other sciences geometrical, such as civil engineering, mechanical engineering and electrical engineering on the other hand in relation to buildings, Where the focus is on the process of integration between various engineering aspects of the building, so as to reach the optimal design, which has the characteristics of durability and safety on the one hand, energy saving and comfort on the other.One of the most important problems facing the engineers is to separate the building systems,  architect who shall design plans without taking into account the structural design or environmental design and a mechanical engineer make his mechanical designs chimes without realizing the importance of the structural side and so on. As the rear overlaps and conflicts in different designs, which may lead to other things that were not foreseen, which affects the function of the building and force or the benefit of the building(serviceability),if we look at the reality, we find that all systems operate as one unit and cannot separate them, The best design is a design that takes into account all the systems, and from this standpoint, we find that the architect, and the skills they learned from the university and from building engineering department in particular, able to be the linking of these systems as required, without affecting any part of the project and thus access to the best design. Human beings have always sought to develop himself, he is always trying to learn and benefit from the expertise around him, so it was and still always consistent work on building new relationships with other people, yet he is always trying to look for ways to entertain himself and those around him. Hence, the idea of creating a distinctive buildings, which combine multiple activities, cultural, Social, recreational, administrative, commercial and residential, etc.    Multi functional buildings are considered as a very important type of buildings in any developing city, Because it has many benefits for residents of the area and the site in general, such as saving time, money, and effort for the population of that region in general , and the residents of the building in particular. This is due to the existence of all functions that they need in the same area.These types of buildings are also friendly with the environment, the short distance that population have to pass every day without any doubt reduce the bad effect of cars pollution on the environment, so it helps to revive the region with a clean environment, away from traffic congestion and exhaust fumes.For these reasons we choose our project to be a multi-functional building, and the primary goal of the project is an integrated building design, environment-friendly, which contains most of the green building standards, and the sub goals are integrated design of all aspects of construction such as structural design, architectural systems, heating and air conditioning, thermal and acoustic insulation, with a focus on environmental aspects in the design, and we will search for new building materials to be used in the building.

Perhaps the urgent need to pursue the rapid technical development in various construction industries which are still witnessing a remarkable progress of time, and discoveries of modern construction, which aims primarily to achieve human well-being, taking into account the growing interest in environmental aspects including the design of green buildings and the resistance to earthquakes, according to planning Strategic Sustainable DevelopmentAs for the engineering department of buildings, you can define a building's architecture as a link between the Architecture, Planning and Landscape Architecture, and between the other sciences geometrical, such as civil engineering, mechanical engineering and electrical engineering on the other hand in relation to buildings, Where the focus is on the process of integration between various engineering aspects of the building, so as to reach the optimal design, which has the characteristics of durability and safety on the one hand, energy saving and comfort on the other.One of the most important problems facing the engineers is to separate the building systems,  architect who shall design plans without taking into account the structural design or environmental design and a mechanical engineer make his mechanical designs chimes without realizing the importance of the structural side and so on. As the rear overlaps and conflicts in different designs, which may lead to other things that were not foreseen, which affects the function of the building and force or the benefit of the building(serviceability),if we look at the reality, we find that all systems operate as one unit and cannot separate them, The best design is a design that takes into account all the systems, and from this standpoint, we find that the architect, and the skills they learned from the university and from building engineering department in particular, able to be the linking of these systems as required, without affecting any part of the project and thus access to the best design. Human beings have always sought to develop himself, he is always trying to learn and benefit from the expertise around him, so it was and still always consistent work on building new relationships with other people, yet he is always trying to look for ways to entertain himself and those around him. Hence, the idea of creating a distinctive buildings, which combine multiple activities, cultural, Social, recreational, administrative, commercial and residential, etc.    Multi functional buildings are considered as a very important type of buildings in any developing city, Because it has many benefits for residents of the area and the site in general, such as saving time, money, and effort for the population of that region in general , and the residents of the building in particular. This is due to the existence of all functions that they need in the same area.These types of buildings are also friendly with the environment, the short distance that population have to pass every day without any doubt reduce the bad effect of cars pollution on the environment, so it helps to revive the region with a clean environment, away from traffic congestion and exhaust fumes. For these reasons we choose our project to be a multi-functional building, and the primary goal of the project is an integrated building design, environment-friendly, which contains most of the green building standards, and the sub goals are integrated design of all aspects of construction such as structural design, architectural systems, heating and air conditioning, thermal and acoustic insulation, with a focus on environmental aspects in the design, and we will search for new building materials to be used in the building.
Multi Story Housing